Analysis of the Effect of Liquidity Ratios and Solvency Ratios on Hedging Decisions - Wildan Army Abdillah (Islamicate Institute, 2025)
This study aims to determine the effect of liquidity (current ratio), solvability (debt to equity ratio) on hedging decisions in mining companies in the Indonesia Stock Exchange 2016-2019 period using binary logistic regression. The total population in this study were 41 mining companies listed on the Indonesia Stock Exchange in the 2016-2019 period. The type of data used is secondary data obtained from the Indonesia Stock Exchange (IDX). Simultaneous significant test results seen from the Omnimbus Test of Model table that there is an influence of liquidity and solvability on hedging decisions, while partially, the variable liquidity (current ratio) has a significant effect, while solvability (debt to equity ratio) has no effect on hedging decisions.